Improving field establishment of cacao (Theobroma cacao) through mulching, irrigation and shading. (7th January 2019) - Acheampong, K.; Daymond, A. J.; Adu-Yeboah, P.; Hadley, P.
Abstract: Establishment of young cacao trees in West Africa can be severely impeded by the onset of the dry season. To address this issue, a field experiment was conducted in Ghana to examine whether different mulch treatments and irrigation applied during the dry season combined with overhead shade could improve survival, early growth and yield of cacao. The mulch treatments used were polyethylene film and coffee husks placed around the young plants. Irrigation was used as a positive control, and no mulching or irrigation was a negative control. Three shade regimes were provided through different arrangements of Gliricidia sepium and plantains. Four different cacao clones were used in the study in a replicated split-plot design. Early growth of cacao was stimulated under the irrigation and plastic mulch treatments. Higher rates of photosynthesis during the dry season appeared to underlie these increases. Significantly higher early yields were also observed under the irrigation and coffee mulch treatments compared with the control. Plant survival varied significantly between treatments; irrigation was associated with the highest plant survival (94%), followed by the plastic mulch treatment (91%), coffee husk (82%) and the control (70%). There was also an increase in survival when more intense shading was used. Under zero mulch conditions, differences in survival were observed between clones. The clones P 30 [POS] and SCA 6 were more sensitive to drought (in terms of survival) than PA 150 and T 79/501. It is concluded that relatively simple mulching techniques or controlled irrigation in conjunction with appropriate shade management can significantly improve early establishment and cropping of cacao.